Cyclodextrin Fundamentals, Reactivity and Analysis (Environmental Chemistry for a Sustainable World,, 2018)
This book is the first volume of two volumes on cyclodextrins published in the series Environmental Chemistry for a Sustainable World. After a brief description of the cyclodextrin fundamentals, the first chapter by Grégorio Crini et al. provides an overview of cyclodextrin research during the last 5 years. The second chapter by Michal Řezanka discusses the synthesis of novel cyclodextrin systems by selective modifications. Then Eric Monflier et al. describes the synthesis of nanostructured porous materials based on cyclodextrins, and applications in heterogeneous catalysis and photocatalysis. The use of thermal analyses for assessing cyclodextrin inclusion complexes is reviewed in chapter 4 by Daniel Hădărugă et al. Experimental methods for measuring binding constants of cyclodextrin inclusion compounds are presented by David Landy. The second volume reviews cyclodextrin applications in medicine, food, environment and liquid crystals.